Efficacy of Disulfiram and Cognitive Behavior Therapy in Cocaine-Dependent Outpatients: A Randomized Placebo-Controlled Trial - Carroll, Kathleen M. (2004)
CONTEXT: Disulfiram has emerged as a promising treatment for cocaine dependence, but it has not yet been evaluated in general populations of cocaine users. OBJECTIVES: To compare the effectiveness of disulfiram therapy with that of a placebo condition in reducing cocaine use and to compare the effectiveness of 2 active behavioral therapies—cognitive behavior therapy (CBT) and interpersonal psychotherapy (IPT)—in reducing cocaine use. DESIGN: Randomized, placebo-controlled, double-masked (for medication condition), factorial (2×2) trial with 4 treatment conditions: disulfiram plus CBT, disulfiram plus IPT, placebo plus CBT, and placebo plus IPT. SETTING: A community-based outpatient substance abuse treatment program. PATIENTS: A total of 121 individuals meeting the criteria for current cocaine dependence. INTERVENTIONS: Patients received either disulfiram (250 mg/d) or placebo in identical capsules. Medication compliance was monitored using a riboflavin marker procedure. Both behavioral therapies (CBT and IPT) were manual guided and were delivered in individual sessions for 12 weeks. MAIN OUTCOME MEASURES: Random regression analyses of self-reported frequency of cocaine use and results of urine toxicology screens. RESULTS: Participants assigned to disulfiram reduced their cocaine use significantly more than those assigned to placebo, and those assigned to CBT reduced their cocaine use significantly more than those assigned to IPT (P<.01 for both). Findings were consistent across all study samples (eg, intention to treat, treatment initiators, and treatment completers). Benefits of disulfiram use and CBT were most pronounced for participants who were not alcohol dependent at baseline or who fully abstained from drinking alcohol during treatment. Adverse effects experienced by participants who received disulfiram were mild and were not considerably different from those experienced by participants who received placebo. CONCLUSIONS: Disulfiram and CBT are effective therapies for general populations of cocaine-dependent individuals. Disulfiram seems to exert a direct effect on cocaine use rather than through reducing concurrent alcohol use.